Binding of Elementary Bodies by the Opportunistic Fungal Pathogen Candida albicans or Soluble β-Glucan, Laminarin, Inhibits Chlamydia trachomatis Infectivity - Kruppa, Michael D.; Jacobs, Jeremy; King-Hook, Kelsey; Galloway, Keleigh; Berry, Amy; Kintner, Jennifer; Whittimore, Judy D.; Fritz, Rolf; Schoborg, Robert V.; Hall, Jennifer V. (Frontiers in Microbiology, 2019)
Microbial interactions represent an understudied facet of human health and disease. In this study, the interactions that occur between Chlamydia trachomatis and the opportunistic fungal pathogen, Candida albicans were investigated. Candida albicans is a common component of the oral and vaginal microbiota responsible for thrush and vaginal yeast infections. Normally, Candida exist in the body as yeast. However, disruptions to the microbiota create conditions that allow expanded growth of Candida, conversion to the hyphal form, and tissue invasion. Previous studies have shown that a myriad of outcomes can occur when Candida albicans interacts with pathogenic bacteria. To determine if C. trachomatis physically interacts with C. albicans, we incubated chlamydial elementary bodies (EB) in medium alone or with C. albicans yeast or hyphal forms for 1h. Following incubation, the samples were formaldehyde-fixed and processed for immunofluorescence assays using anti-chlamydial MOMP or anti- chlamydial LPS antibodies. Replicate samples were replenished with culture medium and incubated at 35oC for 0-120 h prior to fixation for immunofluorescence analysis or collection for EB infectivity assays. Data from this study indicates that both C. trachomatis serovar E and C. muridarum EB bind to C. albicans yeast and hyphal forms. This interaction was not blocked by pre-incubation of EB with the Candida cell wall components, mannan or β-glucans, suggesting that EB interact with a Candida cell wall protein or other structure. Bound EB remained attached to C. albicans for a minimum of 5 days (120h). Infectivity assays demonstrated that EB bound to C. albicans are infectious immediately following binding (0h). However, once bound to C. albicans, EB infectivity decreased at a faster rate than EB in medium alone. At 6h post binding, 40% of EB incubated in medium alone remained infectious compared to only 16% of EB bound to C. albicans. Likewise, pre-incubation of EB with laminarin, a soluble preparation of β-glucan, alone or in combination with other fungal cell wall components significantly decreases chlamydial infectivity in HeLa cells. These data indicate that interactions between EB and C. albicans inhibit chlamydial infectivity, possibly by physically blocking EB interactions with host cell receptors.